Metode Pembelajaran Pendidikan Agama Islam Aktif dan Kreatif di Madrasah Aliyah Darul Ulum Banyuanyar Kecamatan Palengaan Kabupaten Pamekasan - Mutmainah, Hidayatul; Arifin, Samsul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2021)
The problem in this study will reveal the application of active and creative learning methods at Madrasah Aliyah Darul Ulum Banyuanyar Palengaan Pamekasan, this study aims to describe the learning methods applied in Madrasah Aliyah Darul Ulum Banyuanyar. and using descriptive qualitative method with primary data collection through interviews and observations while secondary data obtained through documentation. The results of the study indicate that the application of learning methods in Madrasas has not been effective because they still use conventional methods such as the lecture method, discussion method, and demonstration method. It is necessary to develop a variety of learning methods so that the learning process becomes active and creative